The Effectiveness of NPWT on Burns in Children: A Literature Review - Ristina Mirwanti; Asti Oktavianti; Alex Setiawan; Nada Shofi; Nidya Fildza; Rahmi Fitriyani; Aldiano Alham; Silvia Azkhari (Padjadjaran Acute Care Nursing Journal, 2021)
Burns is a global public health problem, and it is estimated that burns cause 180,000 deaths every year. There are many known wound care techniques, especially in the world of health, which are now constantly developing better by technological developments, consumer demands, and the development of related diseases. Negative Pressure Wound Therapy (NPWT) is a non-invasive therapy that promotes granulation and wound closure. This study aimed to prove the effectiveness of NPWT against burns in children. This study used a literature study approach with a descriptive review type. Based on the search results, seven articles were obtained using keywords, and papers were received from science direct, PubMed, and google scholar. The seven articles were published between 2014-2020, with the research method of each article being a randomized controlled trial and a retrospective study. Based on the results of several research articles, it was found that NPWT (Negative Pressure Wound Therapy) has been proven to be effective in treating burns in children.